Chemical Enhancement of In Vitro and In Vivo Direct Cardiac Reprogramming. Issue 10 (7th March 2017) - Mohamed, Tamer M. A.; Stone, Nicole R.; Berry, Emily C.; Radzinsky, Ethan; Huang, Yu; Pratt, Karishma; Ang, Yen-Sin; Yu, Pengzhi; Wang, Haixia; Tang, Shibing; Magnitsky, Sergey; Ding, Sheng; et al.
Abstract : Background: Reprogramming of cardiac fibroblasts into induced cardiomyocyte-like cells in situ represents a promising strategy for cardiac regeneration. A combination of 3 cardiac transcription factors, Gata4, Mef2c, and Tbx5 (GMT), can convert fibroblasts into induced cardiomyocyte-like cells, albeit with low efficiency in vitro. Methods: We screened 5500 compounds in primary cardiac fibroblasts to identify the pathways that can be modulated to enhance cardiomyocyte reprogramming. Results: We found that a combination of the transforming growth factor-β inhibitor SB431542 and the WNT inhibitor XAV939 increased reprogramming efficiency 8-fold when added to GMT-overexpressing cardiac fibroblasts. The small molecules also enhanced the speed and quality of cell conversion; we observed beating cells as early as 1 week after reprogramming compared with 6 to 8 weeks with GMT alone. In vivo, mice exposed to GMT, SB431542, and XAV939 for 2 weeks after myocardial infarction showed significantly improved reprogramming and cardiac function compared with those exposed to only GMT. Human cardiac reprogramming was similarly enhanced on transforming growth factor-β and WNT inhibition and was achieved most efficiently with GMT plus myocardin. Conclusions: Transforming growth factor-β and WNT inhibitors jointly enhance GMT-induced direct cardiac reprogramming from cardiac fibroblasts in vitro and in vivo and provide a more robust platform for cardiac regeneration. Abstract : Supplemental Digital Content is available in the text.